2011
DOI: 10.1021/ed1007266
|View full text |Cite
|
Sign up to set email alerts
|

Organic Chemistry Educators’ Perspectives on Fundamental Concepts and Misconceptions: An Exploratory Study

Abstract: An exploratory study was conducted with 23 organic chemistry educators to discover what general chemistry concepts they typically review, the concepts they believe are fundamental to introductory organic chemistry, the topics students find most difficult in the subject, and the misconceptions they observe in undergraduate organic chemistry students. The goal of the study was to generate an exploratory overview of current practice in order to spur discussion on organic chemistry curriculum and to encourage furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
90
0
8

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(101 citation statements)
references
References 26 publications
3
90
0
8
Order By: Relevance
“…Studies [24,25] support students' lack of prior knowledge about the number of bonds around a carbon atom. In a survey of college organic chemistry instructors it was found that students indicate that "carbon can have more than or less than four bonds" ( [24], p. 347).…”
Section: Number Of Hydrogen Atoms Bonded To Carbonmentioning
confidence: 94%
See 3 more Smart Citations
“…Studies [24,25] support students' lack of prior knowledge about the number of bonds around a carbon atom. In a survey of college organic chemistry instructors it was found that students indicate that "carbon can have more than or less than four bonds" ( [24], p. 347).…”
Section: Number Of Hydrogen Atoms Bonded To Carbonmentioning
confidence: 94%
“…It is these same topics that have posed a challenge to organic chemistry instructors and provide the motivation for them to review prior general chemistry knowledge [14][15][16][17][18][19][20][21][22][23][24]. The general chemistry concepts they review are listed in Table 1.…”
Section: General Chemistry Concepts Organic Chemistry Instructors Revmentioning
confidence: 99%
See 2 more Smart Citations
“…En la enseñanza de la química orgánica, específicamente en los tópicos de nomenclatura, estructura bi o tridimensional de moléculas, propiedades fisicoquímicas del carbono y reactividad orgánica estudios demuestran algunos obstáculos y concepciones alternativas que poseen los estudiantes sobre algunos procesos característicos fundamentales para la comprensión de la química orgánica. Además, cabe mencionar que la mayoría de estos estudios explicitan las concepciones alternativas que poseen los estudiantes en educación superior (Duis J., 2011;Hernández et al, 2013;Rushton et al, 2008;Treagust et al, 2004;Villaseñor et al, 2013;Zoller U., 1990). Para efectos de este trabajo se incluyeron las investigaciones que podían ser extrapoladas a educación secundaria.…”
Section: Introductionunclassified